Matemática e música: uma reflexão à luz da Teoria dos Registros de Representação Semiótica - Pinto, Ailton Nogueira (2019)
This dissertation aims to investigate teaching proposals that integrate mathematics and music discussion about the dimension they take not only in relation to the teaching of mathematics, but also to the teaching of music in the perspective of the theory of register of semiotic representation. Music as a subject in elementary school was replaced in the 1970s by Art Education, a discipline that favors other artistic manifestations beyond music, which led its teachers to choose or not to teach it, although BNCC relates music to several areas of knowledge Music as a subject in elementary school was replaced by Artistic Education in the 70's, leading schools to privilege or not its teaching, although BNCC relates music to several areas of knowledge. On the other hand, we found that many research works present several initiatives aimed at bringing math and music closer in elementary school, some focused on math teaching, others on music, as ways to overcome the failures and difficulties found in the teaching of both areas. Thus, we need to clarify as to what mathematics can add to musical education, or vice-versa, since official documents do not explicitly assign mathematics to the treatment of logical aspects related to the structure of music nor music to treatments linked to mathematics. Thus, through a bibliographic study we analyzed scientific productions in the field of mathematics education, seeking to identify whether the focus was learning mathematics through music or learning music through mathematics, as well as the relationships between the representations used in both, based on the theory of register of semiotic representation. Confronting the historical, epistemological and theoretical aspects obtained in our literature review, we conclude that the proposals integrating mathematics and music can enhance the learning of mathematics but are not enough for the specificities related to its teaching. These proposals also fail to encompass all dimensions of music, being restricted to the logical-mathematical dimension, strongly present in the theoretical and structural aspects of music. Thus, based on our theoretical framework, we find that these proposals can mobilize different representations of mathematical objects, as well as allow access to different musical semiotic systems, with due reservations that these proposals are not enough for the intended teaching. However, the teaching of music can develop some meaning if articulated with other areas of knowledge, through inter or transdisciplinary proposals that privilege several dimensions related to music, such as perception and creation, essential for an individual to appropriate music education in elementary school